Fibrocytes: A Critical Review and Practical Guide - Reinhardt, James W.; Breuer, Christopher K. (Frontiers in Immunology, 2021)
Fibrocytes are hematopoietic-derived cells that directly contribute to tissue fibrosis by producing collagen following injury, during disease, and with aging. The lack of a fibrocyte-specific marker has led to the use of multiple strategies for identifying these cells in vivo. This review will detail how past studies were performed, report their findings, and discuss their strengths and limitations. The motivation is to identify opportunities for further investigation and promote the adoption of best practices during future study design.